Integrated management of Colocasia (Colocasia esculenta) blight - and S.K. RANA, USHA RANA*, S.K. SUGHA (Indian Phytopathology, 2007)
Studies were conducted during Kharif 2003 and 2004 to evaluate the effect of mulch, corm dip in fungicides, foliar sprays and integration of all components for the management of Colocasia blight (Phytophthora colocasiae). Crop mulching with eupatorium, persian liIiac, eucalyptus, oat straw and wheat straw delayed the appearance of disease by 5-6 days and reduced the severity of disease. Among the different crops used as mulch, Eupatorium - an obnoxious weed proved to be good mulch with significant increase in corm yield and decreased the disease severity. Five fungicides viz. Ridomil MZ, Indofil-M-45, Kavach, Curzate M8 and Blitox-50 were evaluated against Colocasia blight through corm dip and chemical sprays. Among the fungicides evaluated through corm dip, one hour corm dip in Ridomil MZ (metalaxyl 8% + mancozeb 64%) @ 0.3% before sowing resulted ih 46.9 - 50.1% disease control with maximum (6.8 t/ha) corm yield. Three fortnightly sprays of Ridomil MZ recorded maximum disease control (54.6%) with maximum (7.4 t/ha) corm yield. Integration of one-hour corm dip in Indofil M-45, mulching with eupatorium leaves and three fortnightly foliar sprays of Ridomil MZ resulted in 76.9% control of disease with 131.3% increase in crop yield over unprotected crop.